The Effect Of Crossword Puzzle Media On Writing Skills In Arabic Language Learning - Irsyad Hisyam Rakasiwi; Miatin Rachmawati (Jurnal Studi Guru dan Pembelajaran, 2024)
A common issue faced in efforts to improve Arabic writing skills is the lack of appropriate and engaging learning media models that can effectively facilitate the learning process while making it enjoyable for students. This study is a Pre-experimental study involving two classes as an experimental class and a control class using an experimental design "two-Group Pretest-Postest Design" which aims to determine the effect of crossword puzzle learning strategies on Arabic language learning writing skills with a sample of 52 students. The data analysis techniques used are validity test data analysis, reliability test and hypothesis submission such as normality test, homogeneity test, t-test and N-Gain Score test. The results of this study indicate that the validity test with the results of 20 questions r count <0.05. reliability with results of 0.738> 0.7 which means reliable. The discriminatory power is 80% of questions with a sufficient index, 10% of questions with a good index and 10% with a less index. The level of difficulty is 55% of questions with an easy level of difficulty interpretation, 45% of questions with a moderate level of difficulty interpretation and none with a difficult level of difficulty interpretation. normality with the results of the significance data of 0.200 which means that the normality test is greater than 0.05 or 0.200>0.05. Thus it can be concluded that the data is normally distributed. And the homogeneity of the significance data obtained is 0.514 which means that the significance is greater than 0.05 or 0.514>0.05. This shows that the data is homogeneous. So it can be concluded that the crossword puzzle teaching model for the Hamarah Kitabah class X at SMA 4 Muhammadiyah Jakarta has an effect and can improve learning outcomes.